Tanggung Jawab Pidana Terhadap Pelaku dalam Kecelakaan Lalu Lintas di Wilayah Hukum Resor Bangli - I Gede Arimastanaya; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
The level of discipline and understanding of the rules and low courtesy of road users are things that need special attention in their efforts to solve problems in the field of traffic. Various efforts have been carried out by the government to improve traffic conditions in Indonesia but still have not been able to keep up with the rapid development of traffic. Based on the background of the problem above, the problem can be formulated as follows: how are the legal consequences for the perpetrator in a traffic accident whose victims died and how are the legal considerations for the perpetrators in criminal liability for traffic accidents. The type of research used is juridical empirical legal research because in this study, besides based on existing theories, it is also compared with research based on interviews and data in the field. The results of the discussion in this study: The legal consequences for the perpetrators in traffic accidents whose victims died were punished with a minimum prison sentence of 5 years. In accordance with Article 359 of the Criminal Code. Legal considerations for perpetrators in criminal liability against traffic accidents include elements of accident (negligence), never been punished, there is peace between the parties, giving information is not complicated, there are witnesses who lighten, then the threat of punishment can be lighter.